Design, Analysis, and Pitfalls of Clinical Trials Using Ex Situ Liver Machine Perfusion: The International Liver Transplantation Society Consensus Guidelines. Issue 4 (April 2021) - Martins, Paulo N.; Rizzari, Michael D.; Ghinolfi, Davide; Jochmans, Ina; Attia, Magdy; Jalan, Rajiv; Friend, Peter J.; Martins, Paulo N.; Rizzari, Michael; Attia, Magdy; Ghinolfi, David; Jochmans, Ina; et al.
Abstract : Background: Recent trials in liver machine perfusion (MP) have revealed unique challenges beyond those seen in most clinical studies. Correct trial design and interpretation of data are essential to avoid drawing conclusions that may compromise patient safety and increase costs. Methods: The International Liver Transplantation Society, through the Special Interest Group "DCD, Preservation and Machine Perfusion, " established a working group to write consensus statements and guidelines on how future clinical trials in liver perfusion should be designed, with particular focus on relevant clinical endpoints and how different techniques of liver perfusion should be compared. Protocols, abstracts, and full published papers of clinical trials using liver MP were reviewed. The use of a simplified Grading of Recommendations Assessment, Development, and Evaluation working group (GRADE) system was attempted to assess the level of evidence. The working group presented its conclusions at the International Liver Transplantation Society consensus conference "DCD, Liver Preservation, and Machine Perfusion" held in Venice, Italy, on January 31, 2020. Results: Twelve recommendations were proposed with the main conclusions that clinical trials investigating the effect of MP in liver transplantation should (1) make the protocol publicly available before the start of the trial, (2) be adequately powered, and (3) carefully consider timing of randomization in function of the primary outcome. Conclusions: There are issues with using accepted primary outcomes of liver transplantation trials in the context of MP trials, and no ideal endpoint could be defined by the working group. The setup of an international registry was considered vital by the working group.